From Havana to Cádiz in the Imaginary of Women Writers of the Last Decades - María del Mar López-Cabrales; Inmaculada Rodríguez-Cunill (Literature, 2023)
In this essay, we intend to demonstrate how the cities of Havana and Cádiz became mutable literary subjects that accompany the female characters of the narratives of female writers of the past decades from Havana (Anna Lidia Vega Serova, Ena Lucía Portela, and Mylene Fernández Pintado) and Cádiz (Ana Rossetti and Pilar Paz Pasamar). The ironic and delusional visions of a ruined life due to the special period, economic crisis, and political xenophobia in Cádiz will be illustrated by Cuban-Spanish mapping of the analyzed authors’ works. Our hypothesis stems from the idea that there is a clear relation between the representation of the city and political, cultural, and patriarchal transgression that is quoted in these texts (Bataille), which relates to the experience of scarcity/poverty lived on both sides of the Atlantic Ocean. Our bibliographic search has focused on the literary expression of the experience of these cities from the point of view of female writers and protagonists. We concluded with a universal understanding of the experience of the space marked by literature and the gaze of women.